The Role of Banks in the Development of the Food Industry (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The article identifies urgent problems related to the organizational and economic foundations of sustainable development of the food industry in Uzbekistan and develops scientific proposals aimed at solving them.